Analisis Pentingnya Legalistas Usaha (Daftar Izin Usaha) Bagi Perusahaan - Arrizal, Brian Hafiz; Ramadhan, Resa Piska; Fahrurrizkianur, Akhmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Business legality is an important element in running a company legally and competitively. By having a valid business license, the company can operate in accordance with regulations without the risk of legal sanctions, thereby providing legal certainty and protection for the company's rights. Legality also enhances the company's image, builds trust, and opens up opportunities for collaboration with other parties. In addition, several business sectors have specific requirements that mandate business legality. This legality not only protects the company from rights violations but also helps address potential legal issues. In the competitive business world, business legality becomes an aspect that cannot be ignored and must be understood and managed properly.